STRATEGIES IN PREVENTING MONEY POLITICS IN SIMULTANEOUS REGIONAL ELECTIONS IN PALU CITY - Nasrullah, Nasrullah; Rusdin, Rusmawaty Bte (UIN Sunan Gunung Djati, 2024)
In the recent elections, money politics has become one of the topics of public interest. Money politics is used to win large numbers of votes and maintain control of Pilkada. This research aims to provide solutions to avoid money politics in the Simultaneous Regional Elections in Palu City in 2020, as well as examine the elements that encourage and hinder the prevention of money politics in the regional elections. This study uses a qualitative approach. Using observation, interviews, and documentation studies as data collection methods. Miles and Huberman's approach to data analysis includes data collection, data reduction, data display, and data verification. Based on the findings, the policy strategy used in money politics is carried out through four efforts: dissemination of violations, participatory supervision, surveillance patrols, and firm law enforcement.